Aqueous Extract of Rhubarb Promotes Hepatotoxicity via Facilitating PKM2-Mediated Aerobic Glycolysis in a Rat Model of Diethylnitrosamine-Induced Liver Cancer [Letter] - Geng S; Zhu Y; Zheng Y (Drug Design, Development and Therapy, 2024)
Shiyu Geng,1 Ying Zhu,1 Yi Zheng2 1School of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou, People’s Republic of China; 2Department of Infectious Disease, The Second Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, People’s Republic of ChinaCorrespondence: Yi Zheng, Department of Infectious Disease, The Second Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, People’s Republic of China, Email zhengyi_wzh@yeah.net